The negative effect of Akkermansia muciniphila-mediated post-antibiotic reconstitution of the gut microbiota on the development of colitis-associated colorectal cancer in mice - Wang, Kaicen; Wu, Wenrui; Wang, Qing; Yang, Liya; Bian, Xiaoyuan; Jiang, Xianwan; Lv, Longxian; Yan, Ren; Xia, Jiafeng; Han, Shengyi; Li, Lanjuan (Frontiers in Microbiology, 2022)
The bidirectional relationship between colorectal cancer (CRC) and the gut microbiome has been well-documented. Here, we investigated the impact of Akkermansia muciniphila-mediated postantibiotic gut microbial reconstitution on the development of colitis-associated CRC (CAC). The results showed that postantibiotic replenishment of A. muciniphila worsened the tumorigenesis of CAC, as indicated by an increased number of large (>2 mm in diameter) tumors and both average and total tumor diameters. Measures of intestinal barrier function showed that postantibiotic A. muciniphila gavage damaged the intestinal barrier as reflected by lower transcriptional levels of Tjp1, Ocln, Cdh1, and MUC2. Impaired gut barrier followed by LPS translocation as indicated by higher level of serum LBP. The increased colonic mRNA levels of Il1b, Il10, and Tnfa and serum level of IL-1b, IL-6, and TNF-a indicated postantibiotic A. muciniphila replenishment resulted in an overactivated inflammatory environment in CAC. Analysis of the evolution of the microbial community during the progression of CAC showed that postantibiotic supplementation of A. muciniphila led to a distinct microbial configuration when compared with other treatments characterized by enriched Firmicutes, Lachnospiraceae, and Ruminococcaceae, whereas depleted Bacteroidetes, accompanied by a higher Firmicutes/ Bacteroidetes (F/B) ratio. Furthermore, postantibiotic A. muciniphila administration changed the bile acids (BA) metabolic profile as indicated by decreases in the concentration of secondary BA (SBA) and w-murocholic acid (wMCA), murocholic acid (muroCA). In addition, A. muciniphila supplementation after antibiotics pretreatment also impacted the metabolism of short-chain fatty acids (SCFAs) as evidenced by increases in the concentrations of acetic acid, propionic acid, butyric acid, and valeric acid. Our work surprisingly observed that A. muciniphila-mediated postantibiotic reconstitution of the gut microbiota aggravated CAC in mice and it might exert its effect through damaging the gut barrier, exacerbating inflammatory responses, disrupting the postantibiotic recovery of the microbial community, and further influencing the metabolism of BA and SCFAs. This finding indicated that maintaining the homeostasis of the intestinal microorganisms is more crucial to health than replenishing a single beneficial microbe and that probiotic should be used with caution after antibiotic treatment.